Standardized Application of Laxatives and Physical Measures in Neurosurgical Intensive Care Patients Improves Defecation Pattern but Is Not Associated with Lower Intracranial Pressure. (31st December 2014) - Kieninger, Martin; Sinner, Barbara; Graf, Bernhard; Grassold, Astrid; Bele, Sylvia; Seemann, Milena; Künzig, Holger; Zech, Nina
Abstract : Background . Inadequate bowel movements might be associated with an increase in intracranial pressure in neurosurgical patients. In this study we investigated the influence of a structured application of laxatives and physical measures following a strict standard operating procedure (SOP) on bowel movement, intracranial pressure (ICP), and length of hospital stay in patients with a serious acute cerebral disorder. Methods . After the implementation of the SOP patients suffering from a neurosurgical disorder received pharmacological and nonpharmacological measures to improve bowel movements in a standardized manner within the first 5 days after admission to the intensive care unit (ICU) starting on day of admission. We compared mean ICP levels, length of ICU stay, and mechanical ventilation to a historical control group. Results . Patients of the intervention group showed an adequate defecation pattern significantly more often than the patients of the control group. However, this was not associated with lower ICP values, fewer days of mechanical ventilation, or earlier discharge from ICU. Conclusions . The implementation of a SOP for bowel movement increases the frequency of adequate bowel movements in neurosurgical critical care patients. However, this seems not to be associated with reduced ICP values.